Leaders and followers in the effectiveness of public safety services in European states: A spatial frontier approach - Agata Żółtaszek (Comparative Economic Research. Central and Eastern Europe, 2014)
Public safety is an important factor in both public and private life. Simultaneously it is one of the most regionally diverse sectors, due to historical, cultural, social, legal, and financial differences.Therefore, it is very difficult to compare public safety policies and facilities directly. However, assessment and comparison are crucial factors for defining the best practices and implementing the "learning-from-the-best" policy, which is important in the process of regional development and globalization. Fortunately some quantitative methods, such as DEA (Data Envelopment Analysis) enable this kind of research. DEA allows for analyzing relative effectiveness based on inputs and outputs, without incorporating procedural specifics of public safety. Therefore, the aim of this paper is to perform a regional analysis of the technical effectiveness of public safety systems in European states in 2003 and 2012 by utilizing an optimization method of DEA. Based on the results of this research countries are divided into two groups - effective and ineffective. Countries with effective systems are considered leaders. They present best practices which should be treated as benchmarks for the countries with ineffective systems, i.e. followers. In the research, inputs of the Data Envelopment Analysis consist of human and financial resources, as these are crucial for the functioning of public safety systems. The outputs are transformations of major crime categories. The analysis has been carried out for selected European countries in 2003 and 2012. This analysis indicates that among the countries with effective public safety systems are Finland, Norway, Romania and Poland.The worst technical efficiency could be observed in Belgium, the UK, Estonia, and Italy, which are underperforming and wasting a large proportion of their resources. This research indicates that despite many differences among states' public safety policies, improvement and regional development can be stimulated and achieved by implementing the "learning-from-the-best" policy.
Keywords: 330; regional analysis; public safety; economics of crime; Data Envelopment Analysis (DEA)